Beethoven - Carew-Miller, Anna.
A biography of the German composer who was inspired by personal tragedies to create great musical compositions.
Keywords: Beethoven, Ludwig van, -- 1770-1827 -- Juvenile literature; Beethoven, Ludwig van, -- 1770-1827.; Composers -- Austria -- Biography -- Juvenile literature; Composers